The Impact Of Cognitive Apprenticeship Strategy On The Desire To Learn And Cognitive Depth In Social Studies Among Second-Grade Intermediate Students - Obaid Al-Hamzawi, Wissam Aziz (Universitas Islam Tribakti Lirboyo Kediri, 2024)
The aim of this research is to learn about the impact of the cognitiveapprenticeship strategy on the desire for learning and the knowledgedepth in the subject of sociology in students of the second grade. To thisend, two hypotheses have been formulated: There is no statisticallysignificant difference at the level of (0.05) between the average grades ofthe pilot group students who examined the planned article by adopting thecognitive apprenticeship strategy and the control group students whostudied the same subject by adopting the usual method of desire to learnthe subject of sociology. There is no statistically significant difference atthe level of (0.05) between the average grades of the pilot group studentswho examined the planned article by adopting the cognitiveapprenticeship strategy and the control group students who studied thesame subject by adopting the usual method of knowledge depth. Toachieve the two research hypotheses, follow the pilot curriculum andchoose the partially tuned design and after the school has been selected() randomly and after selecting Division (a) to represent the pilot groupconsisting of (33) Student after the exclusion of the students of thedepositors and Division (c) to represent the control group consisting of(32) A student after the exclusion of the students, after the achievement ofinternal and external safety, after the creation of two tools that have thesincerity and consistency of one to measure the desire for learning andknowledge depth. After the application of the experiment to the finalresearch sample, the tools were applied in their final form and after thecorrection of the forms and the discharge and analysis of data in the lightof the SPSS-26 program. Through the results of the research, it wasfound that there is a statistically significant difference between theaverage students of the experimental group and the students of thecontrol group at the level of significance (0.05) in the scale of the desire tolearn and in favor of the experimental group, as it turns out that there is astatistically significant difference between the average students of theexperimental group and students of the control group at the level ofsignificance (0.05) in the cognitive depth test and in favor of theexperimental group, In the light of this, recommendations and proposalswere developed.